Epidural blood patch for spontaneous intracranial hypotension with chronic subdural haematoma: A case report and literature review - Zhang, Jian (J Int Med Res, 2016)
Spinal leakage of cerebrospinal fluid (CSF) is considered to be the primary cause of spontaneous intracranial hypotension (SIH). Subdural haematoma (SDH) is a serious complication of SIH. This current report presents a case of bilateral SDH with SIH that was treated with epidural blood patching (EBP). A 43-year-old male complained of experiencing orthostatic headaches for 2 months without neurological signs. The patient worsened in a local hospital and was transferred to the Sir Run Run Hospital. Brain computed tomography showed bilateral SDH with a midline shift. The patient underwent emergency trephination in the left frontal temporal region. Postoperative magnetic resonance myelography showed a CSF leak originating at the T11–L2 level. As a consequence of clinical deterioration of the patient, EBP was subsequently performed at the T12–L1 level. The headache was rapidly relieved and later the SDH was completely absorbed. This case report and literature review aims to remind clinicians that SIH can cause SDH and that EBP is a viable treatment option.